About the research activity of students of the direction "Pedagogical Education" - Andrafanova N. V., Steklova N. D. (Pedagogical experience: theory, methodology, practice, 2016)
one of professional activities of the future bachelors studying at the direction "Pedagogical education" is a research activity. This article describes the course work as a form of teaching and research activities of students. As a subject of study dynamic geometry system (DGS) is chosen, the application of which in the educational process defines professional standards and the concept of mathematical education in Russia. Investigation of possibilities of DGS in the educational process contributes to the formation of professional competencies in the research activity of bachelors of the direction "Pedagogical Education".
Keywords: исследовательская деятельность; GeoGebra; GeoGebra; Research activity; система динамической геометрии; движение плоскости; курсовая работа; dynamic geometry system; course work; the movement of the plane